2021
DOI: 10.1097/phm.0000000000001705
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison Between the Effect of Combined Chain Exercises Plus Kinesio Taping With Combined Chain Exercises Alone in Knee Osteoarthritis

Abstract: Objective: This study aimed to examine the effect of Kinesio taping as an adjunct to combined chain exercises compared with combined chain exercises alone in the management of individuals with knee osteoarthritis. Methods: A total of 60 (27 male, 33 female) individuals (age range = 50-71 yrs and mean age = 54.26 ± 8.83 yrs) diagnosed as having mild to moderate knee osteoarthritis (based on the Kellgren and Lawrence grade I-III classification) were randomly allocated into two groups with 30 participants each in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 53 publications
0
4
1
Order By: Relevance
“…The addition of wedge insoles to the treatment regimen aimed to further reduce the load on the medial knee compartment, thereby alleviating pain and improving function. Although previous studies indicated that lateral wedge insoles could effectively reduce the external knee adduction moment and improve knee biomechanics (16), this study found that the combination of exercise and Kinesio tape without wedge insoles produced superior outcomes. This discrepancy might be attributed to variations in patient adherence, the degree of knee malalignment, or the specific characteristics of the insoles used.…”
Section: Discussioncontrasting
confidence: 81%
“…The addition of wedge insoles to the treatment regimen aimed to further reduce the load on the medial knee compartment, thereby alleviating pain and improving function. Although previous studies indicated that lateral wedge insoles could effectively reduce the external knee adduction moment and improve knee biomechanics (16), this study found that the combination of exercise and Kinesio tape without wedge insoles produced superior outcomes. This discrepancy might be attributed to variations in patient adherence, the degree of knee malalignment, or the specific characteristics of the insoles used.…”
Section: Discussioncontrasting
confidence: 81%
“…On assessment for the test of normality of dataset, 12 (15.8%) studies [ 25 , 26 , 32 , 38 , 40 , 41 , 52 , 54 , 63 , 69 , 70 , 84 , 96 ] performed a normality test. Eleven of them [ 22 , 32 , 38 , 40 , 41 , 52 , 54 , 63 , 69 , 70 , 84 , 96 ] used the Shapiro–Wilk test while Abdulahi [ 38 ] employed Kolmogorov test. Besides the lack of normality test.…”
Section: Resultsmentioning
confidence: 99%
“…Off-road motorcycling is considered a well-known sport, and because prevention is better than cure, the best support for these athletes could be the implementation of clinical joint examination in the limbs and spine instead of focusing primarily on the cardiorespiratory system [ 40 , 41 ]. Aware of the literature debate around Kinesio taping’s effect on musculoskeletal disorders [ 42 , 43 , 44 , 45 , 46 , 47 ], we decided to utilize it as a support therapy in the pain management administered through antalgic therapy based on the evidence reported by many authors about the positive effect of Kinesio taping application in conjunction with exercises [ 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ], and its validity in the treatment and prevention of spine injuries [ 56 , 57 , 58 , 59 ]. Nevertheless, for low back pain treatment, the kinesiological approach, i.e., exercise administration, is strongly suggested because it effectively generates improvements compared with manual therapy or conservative treatment [ 60 , 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%